2022
DOI: 10.3390/cancers14246254
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Nanosecond Bleomycin Electrochemotherapy and its Effects on Changes in the Immune System and Survival

Abstract: In this work, a time-dependent and time-independent study on bleomycin-based high-frequency nsECT (3.5 kV/cm × 200 pulses) for the elimination of LLC1 tumours in C57BL/6J mice is performed. We show the efficiency of nsECT (200 ns and 700 ns delivered at 1 kHz and 1 MHz) for the elimination of tumours in mice and increase of their survival. The dynamics of the immunomodulatory effects were observed after electrochemotherapy by investigating immune cell populations and antitumour antibodies at different timepoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…Additionally, ensuring a homogeneous treatment is challenging, especially with non-invasive electrodes and highly heterogeneous tissue structures [ 19 ]. To compensate, higher frequency pulses can be used for impedance mitigation and equivalent efficacy nanosecond pulse protocols can be derived, which was confirmed in vitro [ 20 , 21 , 22 , 23 ] and in vivo [ 19 , 24 , 25 , 26 , 27 , 28 ]. High-frequency short-duration protocols show potential advantages compared to standard EP treatment, such as minimized thermal damage [ 29 ], reduced neuromuscular stimulation [ 30 ], lower Joule heating [ 31 ], and most importantly, a more homogeneous response with high flexibility in parametric protocol design.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Additionally, ensuring a homogeneous treatment is challenging, especially with non-invasive electrodes and highly heterogeneous tissue structures [ 19 ]. To compensate, higher frequency pulses can be used for impedance mitigation and equivalent efficacy nanosecond pulse protocols can be derived, which was confirmed in vitro [ 20 , 21 , 22 , 23 ] and in vivo [ 19 , 24 , 25 , 26 , 27 , 28 ]. High-frequency short-duration protocols show potential advantages compared to standard EP treatment, such as minimized thermal damage [ 29 ], reduced neuromuscular stimulation [ 30 ], lower Joule heating [ 31 ], and most importantly, a more homogeneous response with high flexibility in parametric protocol design.…”
Section: Introductionmentioning
confidence: 83%
“…In order to compensate for the lack of significant electrophoretic components and increase the stability and size of the pores, a new modality of high-frequency electroporation (MHz range) can be used [ 45 , 46 ]. Previously, we have shown that high-frequency nsECT with bleomycin can be as good or superior to ESOPE protocols [ 27 ]. However, calcium electroporation is gaining more and more popularity due to accessibility and the capabilities to modulate a systemic immune response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations